Penciptaan Busana Evening Wear Berbahan Embossed Velvet Upholstery dengan Sumber Ide Pura Luhur Poten - Dea Cesayrisa Firmanartha; Inty Nahari; Mein Kharnolis; Ma’rifatun Nashikhah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to create evening wear designs based on local cultural concepts, inspired by the architecture of Pura Luhur Poten at Mount Bromo. Exploration of an unconventional material, embossed velvet upholstery, was conducted using a practice-led research method, including exploration, design, and realization stages. Techniques such as pleating, tucking, and quilting were applied to represent the architectural elements of the temple. The results consist of three designs—one for men and two for women—with A and H silhouettes that blend traditional and modern elements. Gray and red colors were chosen to reflect the characteristics of Pura Luhur Poten. This study demonstrates that local cultural values can be interpreted into fashion designs that are both aesthetic and philosophical.